FIRST INSTRUMENTAL AERIAL SURVEY OF RINGED SEALS (PUSA HISPIDA) AND BEARDED SEALS (ERIGNATHUS BARBATUS) IN THE RUSSIAN ZONE OF THE CHUKCHI AND EAST-SIBERIAN SEAS IN SPRING 2016 - V. I. Chernook; I. S. Trukhanova; A. N. Vasiliev; D. I. Litovka; D. M. Glazov; V. N. Burkanov (Известия ТИНРО, 2019)
An instrumental aerial survey was conducted in the Russian part of the Chukchi Sea and the eastern East-Siberian Sea in the spring of 2016 to investigate new technical capabilities for estimating abundance and distribution of ringed and bearded seals on the spring ice. Density of both species decreased with distance to the mainland; the largest concentrations of ringed seals were detected in coastal waters, including the Koluchinskaya and Chaunskaya Bays. Taking into account the portion of seals in the water (on average 32 %) and the portion of seals that were disturbed by the aircraft engine noise and dove (on average 30.2 % of ringed seals and 5.9 % of bearded seals), the number of ringed seals in the surveyed area was estimated as 50,839 (СI 95 %: 25,400–73,859; CV = 23.8 %), and the number of bearded seals as 14,590 (CI 95 %: 6,404–24,560; CV = 31.1 %). These estimates are considered to be biased low, primarily due to asynchronic collapse of the ringed seal snow lairs in different parts of the surveyed area, which caused a highly variable detection probability of this species that was difficult to account for.